Board Size, Outside CEO and Financial Performance in Family Companies with Enterprise Risk Management (ERM) as a Moderating Variable - Oktriasih, Charisma; Ismiyanti, Fitri (UMSurabaya Publishing, 2024)
This study examines the influence of board size and non-family CEOs (outside CEOs) on the company's financial performance, as well as the moderating effect of enterprise risk management (ERM) in family firms. Financial performance is proxied by return on assets (ROA) as the dependent variable. The sample of this study is family firms from the non-financial sector listed on the Indonesia Stock Exchange (IDX) for the years 2017–2021. For testing the hypothesis, this study uses the Ordinary Least Squares (OLS) and Moderated Regression Analysis (MRA) methods with the application IBM SPSS Statistics 22 for Windows. This study's results show that board size has a positive and significant effect on financial performance in family firms. Meanwhile, the presence of an outside CEO does not have a significant influence on financial performance in family firms. Regarding the moderating effect of ERM, this study shows that ERM does not significantly moderate the influence of board size and an outside CEO on financial performance in family firms